Heterogeneity in Multiple Sclerosis: Scratching the Surface of a Complex Disease. (28th October 2010) - Disanto, Giulio; Berlanga, Antonio J.; Handel, Adam E.; Para, Andrea E.; Burrell, Amy M.; Fries, Anastasia; Handunnetthi, Lahiru; De Luca, Gabriele C.; Morahan, Julia M.
Abstract : Multiple Sclerosis (MS) is the most common demyelinating disease of the central nervous system. Although the etiology and the pathogenesis of MS has been extensively investigated, no single pathway, reliable biomarker, diagnostic test, or specific treatment have yet been identified for all MS patients. One of the reasons behind this failure is likely to be the wide heterogeneity observed within the MS population. The clinical course of MS is highly variable and includes several subcategories and variants. Moreover, apart from the well-established association with the HLA-class II DRB1*15:01 allele, other genetic variants have been shown to vary significantly across different populations and individuals. Finally both pathological and immunological studies suggest that different pathways may be active in different MS patients. We conclude that these "MS subtypes" should still be considered as part of the same disease but hypothesize that spatiotemporal effects of genetic and environmental agents differentially influence MS course. These considerations are extremely relevant, as outcome prediction and personalised medicine represent the central aim of modern research.